Polityka oświatowa III RP jako czynnik erozji kapitału społecznego - Śliwerski, Bogusław (Annales. Etyka w Życiu Gospodarczym, 2010)
The essential for building the society – the category of social capital, becomes a base for educational politics in Poland in new structural conditions after 1989. Author reminding ideological and axiological assumption our oppositional environments from period of socialism, which within the confines of social movement „Solidarity’80” designed educational solutions, that should be introduced in free country. First of all, there was an idea of decentralization the school system and bringing autonomy of school. The most important was the possibility of creating the democratic process of social adaptation for new generation. But surprised our freedom, we forgotten about fundamental principles. In this case actually we have: an agreement for simulative educational changes, substitute ideological centralism for pseudo-democracy, artificial autonomy of school, and manipulating teachers environment by authorities of education departments each and every political party.